MAINTENANCE MANAGEMENT ASSISTANCE FOR IMPROVING MONITORING OF LANDSIDE AREA FACILITIES AT I GUSTI NGURAH RAI AIRPORT BALI - Anggreni, Ni Putu Richa; Putri, Putu Indah Dianti; Dharmayasa, I Gusti Ngurah Putu (LPPM Univ. Ibn Khaldun Bogor, 2023)
I Gusti Ngurah Rai Airport on the island of Bali, an important gateway for tourism in Indonesia, faces challenges in managing landside facilities to support the growing number of passengers. In this study, we investigate the implementation of maintenance management assistance at I Gusti Ngurah Rai Airport in Bali and its impact on facility inspections in rural areas. The research method collects information through interviews, observation and analysis of relevant documents. The conclusion of this study is that maintenance management assistance is an effective way to overcome ground facility control problems at I Gusti Ngurah Rai Airport in Bali.The significance of this research lies in the importance of continuity of maintenance management assistance to maintain the quality of facilities and provide the best experience for all airport users.